2018
DOI: 10.1103/physreva.97.032122
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of accelerated wave packets

Abstract: Wave-packet scattering from a stationary potential is significantly modified when the wave packet is subject to an external time-dependent force during the interaction. In the semiclassical limit, wave-packet motion is simply described by Newtonian equations, and the external force can, for example, cancel the potential force, making a potential barrier transparent. Here we consider wave-packet scattering from reflectionless potentials, where in general the potential becomes reflective when probed by an accele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…However, the most amazing effects, such as invisibility, could be realized only when considering NH potentials. Recently, wave reflection and scattering from complex potentials has sparked a great interest with the prediction of intriguing phenomena, such as unidirectional or bidirectional invisibility of the potential [8][9][10][11][12][13][14][15][16][17][18][19][20][21], asymmetric scattering [22][23][24], constant-intensity wave transmission across suitably engineered NH scattering landscapes [25][26][27][28][29][30], reflectionless transmission based on the spatial Kramers-Kronig relations [31][32][33][34][35][36][37][38][39][40][41][42][43][44]46,47], and NH transparency [48].…”
Section: Introductionmentioning
confidence: 99%
“…However, the most amazing effects, such as invisibility, could be realized only when considering NH potentials. Recently, wave reflection and scattering from complex potentials has sparked a great interest with the prediction of intriguing phenomena, such as unidirectional or bidirectional invisibility of the potential [8][9][10][11][12][13][14][15][16][17][18][19][20][21], asymmetric scattering [22][23][24], constant-intensity wave transmission across suitably engineered NH scattering landscapes [25][26][27][28][29][30], reflectionless transmission based on the spatial Kramers-Kronig relations [31][32][33][34][35][36][37][38][39][40][41][42][43][44]46,47], and NH transparency [48].…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated theoretically that a class of isotropic, inhomogeneous 1D susceptibility profiles can be used to achieve omnidirectionally reflectionless absorption without any gain region, as long as they satisfy the spatial Kramers–Kronig (KK) relations. [ 23–28 ] Recent studies demonstrated experimentally that such spatial KK media can be implemented in a broadband frequency range by constructing passive gradient mesoscopic structures. [ 29,30 ] However, it is still difficult to use these KK media to absorb radiated waves in free space background due to the impedance mismatching at the truncation boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Kramers-Kronig (KK) relations. [23][24][25][26][27][28] Recent studies demonstrated experimentally that such spatial KK media can be implemented in a broadband frequency range by constructing passive gradient mesoscopic structures. [29,30] However, it is still difficult to use these KK media to absorb radiated waves in free space background due to the impedance mismatching at the truncation boundaries.…”
Section: Introductionmentioning
confidence: 99%